RESPON PERTUMBUHAN DAN HASIL SELADA (LACTUCA SATIVA L.) TERHADAP INTERVAL WAKTU APLIKASI PEMBERIAN AIR CUCIAN BERAS - Jumawati, Riana; Paulina, Maria (Jurnal Agroteknologi dan Pertanian (JURAGAN), 2020)
Lettuce is one of the most popular vegetables from various groups, because it does not need special preparation to enjoy it immediately. Its cultivation is relatively easy and does not require special techniques, making lettuce can be grown in polybags or hydroponically. Rice washing water, which is usually not utilized, actually has the potential as liquid organic fertilizer. Besides being practical and environmentally friendly, liquid organic fertilizer can be applied easily. This study aims to determine the effect of the appropriate application time interval for giving rice washing water on the growth and yield of lettuce. This research was conducted in August-October 2020 using polybags containing soil: manure: husk (1: 1: 1). The design used was a single factor completely randomized block design (RAKL). The factor is the application time interval for giving rice washing water with 4 levels, namely: W0 = without giving rice washing water (control), W1 = once every 2 days, W2 = once every 4 days and W3 = once every 6 days with a dose of 50 ml polybag-1. The results showed that the time interval treatment with washing rice water had no significant effect on plant height, number of leaves, diameter, fresh root weight, and total fresh weight of lettuce plants. However, the treatment of giving rice washing water at an interval of 6 days (W3) once showed a better value than without treatment, the time interval for giving rice washing water once every 2 days or 4 days.